Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Polanyi defanged - Turner, Stephen (Social Studies of Science (Sage Publications, Ltd.), 2012)
A literary criticism of the book "Michael Polanyi and His Generation: Origins of the Social Construction of Science," by Mary Jo Nye is presented. The author discusses the significance of Michael Polanyi in the history of science studies and provides insight on his life and his relationship with his brother Karl. He analyzes how the book presents the origins of science studies, Polanyi’s activities as an economist, and his fight against Communism.
Keywords: Dahomey and the Slave Trade; James Bryant Conant; Karl Polanyi; Michael Polanyi & His Generation: Origins of the Social Construction of Science (Book); NYE, Mary Jo; POLANYI, Michael, 1891-1976; communism & science; economists; planning of science; science - study & teaching

A second double movement? Polanyi and shifting global opinions on neoliberalism - Levien, Michael; Paret, Marcel (International Sociology, 2012)
Karl Polanyi’s theory of the ‘double movement’ has gained great currency in recent years to explain the global growth of contemporary social movements resisting neoliberalism. However, there has been no statistical research demonstrating whether these protest movements represent a more general trend of growing discontent with ‘disembedding’ markets from public control. This article uses questions from the World Values Survey to construct an ‘embeddedness’ index measuring public opinion on the desired relationship between states and markets. Focusing on public opinion in 20 countries during the 1990s, the analysis poses three questions: First, is there evidence of increasing global support for ‘re-embedding’ markets? Second, how does such opinion vary across regions of the world? Finally, what is the class and gender composition of this latent countermovement? The results provide substantial evidence of an emerging countermovement in public opinion over the 1990s with complex class, gender, and geopolitical variation.
Keywords: countermovement; double movement; embeddedness; neoliberalism

Consumer markets and national income inequality: A study of 18 advanced capitalist countries - Kollmeyer, Christopher (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2012)
Sociologists have paid scant attention to the possibility that the structure of the macro-economy is an important determinant of income inequality. Although prior research finds negative links between the size of the public sector and income inequality, no study to date considers whether the size of consumer markets has distributional consequences as well. To investigate this possibility, the present study measures the size of national consumer markets with the System of National Accounts used by governments to calculate gross domestic product (GDP). Based on data from 18 advanced capitalist countries over nearly a 40-year period, two-way random effects regression models reveal a strong and positive link between the size of consumer markets and income inequality. This finding is robust to the inclusion of numerous control variables, and to the consideration of endogeneity within the causal relationship. The proposed theoretical explanation centers on ideas developed by Polanyi, and suggests that economic activity in consumer markets creates higher levels of individual differentiation, and hence higher levels of income inequality, than economic activity in other sectors of the economy. The study concludes by highlighting ways future research can advance our theoretical and empirical understanding of this topic.
Keywords: Keynesian economics; Keynesianism; consumer goods; consumer markets; distributive justice; economic aspects; economic sociology; equality - economic aspects; income distribution; income inequality; markets - social aspects; research; social classes; social stratification

Problems and opportunities in Polanyian analysis today - Holmes, Christopher (Economy & Society, 2012)
The three books under review in this article all demonstrate the beginnings of a shift in the tone of literature on or derived from the work of Karl Polanyi. On one hand, the authors all show a willingness to admit a variety of problems and weaknesses in his work. But on the other hand, it is precisely this degree of critical introspection that enables the authors under review to identify some of the most important and contemporarily relevant aspects of Polanyi's thought. In the two main sections of this article – on Polanyi's concepts of ‘embeddedness’ and ‘double movement’ – I define the problems highlighted in previous iterations of Polanyian literature, moving on to examine how the texts under review address those problems, laying particular emphasis on the ideational components of Polanyi's thought. I conclude by suggesting future directions for Polanyian scholarship, mooting the possibility of a distinctively ‘post-Polanyian’ perspective in which ideas, discourse and framing are placed centre stage.
Keywords: DALE, Gareth; HANN, Chris; HART, Keith; Karl Polanyi: The Limits of the Market (Book); Market & Society: The Great Transformation Today (Book); book review; discourse; double movement; economic anthropology: history, ethnography, critique; economic ideas; embeddedness; nonfiction; post-Polanyi

Development Theory and the Constitution of Market Society: A Polanyian View - Scott, Alan (Comparative Sociology, 2012)
Abstract This paper argues that development studies could benefit from a closer engagement with the arguments of Karl Polanyi. Firstly, a Polanyian perspective gives greater weight to non-economic and non-material factors in making, maintaining and modifying markets. Secondly, it focuses research on the problematic, state- sponsored and contested process of bringing the market actor into being. Finally, a Polanyian approach might better link a, broadly speaking, leftist analysis to 'real world' policy debates about the relative balance between market freedoms and regulation. The conclusion elaborates this final point.
Keywords: POLANYI, Karl, 1886-1964; development; disembedding and reembedding; economic development; financial crises; globalization; market making and modifying; mixed economy; neoliberalism; regulation

Economic and Ecological Crises: Green new deals and no-growth economies - Jessop, Bob (Development, 2012)
Bob Jessop applies cultural political economy to the global economic and ecological crisis. He presents theoretical preliminaries concerning economic and ecological imaginaries, and then goes on to highlight the multidimensional nature of the current crisis and struggles over its interpretation.
Keywords: cultural political economy; ecological imaginary; economic imaginary; finance-dominated accumulation; finance-led accumulation; green new deal; neoliberalism; post-neoliberalism

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Keywords: BLOCK, Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Varieties of What? Should We Still Be Using the Concept of Capitalism? - Block, Fred (Political Power & Social Theory, 2012)
This article argues that social scientists should reconsider the analytic value of the term "capitalism." The paper argues that the two most coherent definitions of capitalism are those derived from classical Marxism and from the Worm System theory of Immanuel Wallerstein. Marx and Engels' formulation was basically a genetic theory in which the structure of a mode of production is determined by the mode of surplus extraction. During the course of the 20th century, however, Marxist theorists had to modify this framework and the result has been an uncomfortable hybrid. Wallerstein resolved these tensions by redefining capitalism in terms of the logic of a worm system. However, his argument has difficulty in explaining the consequential variations over time in the specific rules and institutional structures that operate at the global level. The article goes on to argue in favor of Karl Polanyi's concept of market society because it focuses attention on the political governance of market societies at both the national and the global levels.
Keywords: Marxist philosophy; capitalism; mixed economy; political science; public administration; variational principles

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Marx, Weber, and the "Ceaseless Accumulation of Capital." - Ho-Fung Hung (Political Power & Social Theory, 2012)
Seeing capitalism as a system defined by the imperative of the ceaseless accumulation of capital, instead of using the definition based on wage labor or international trade as Block questions, I argue that the concept of capitalism is still too useful to be abandoned, and cannot be replaced by the Polanyian concept of market in our critique of political economy. As Fernand Braudel and Giovanni Arrighi contend, the capitalist logic of capital accumulation, which is affined to monopoly and state power, is antithetical to the logic of market exchange, which is decentralized and prioritizes livelihoods over profits. Historically, capitalism sometimes made use of the market and sometimes subjugated the market to facilitate accumulation. Likewise, globalization today is a combined movement of expanding free market in certain aspects of life through financial deregulation, privatization, trade liberalization, etc. on the one hand, and exclusion of various processes and costs outside the market through revival of extra-economic coercion, externalization of environmental costs, etc., on the other hand. The imperative of capital accumulation drive capitalists and capitalist states to foster marketization and demarketization in different times and spaces. The critique of and resistance to our capitalist system needs to be antimarket in some instances and pro-market in others. A Polanyian critique of the free market is surely powerful and helpful, but it is not enough for our full understanding of the economic malaises of our times. It is at best counterproductive to throw away the concept of capitalism altogether.
Keywords: ARRIGHI, Giovanni; BLOCK, Fred; BRAUDEL, Fernand, 1902-1985; capitalism; economics; globalization; international trade; wages

Dispossession, Class Formation, and the Political Imaginary of Colombia's Coffee Producers Over the Longue Durée: Beyond the Polanyian Analytic - Hough, Phillip A.; Bair, Jennifer (Journal of World-Systems Research, 2012)
For more than a decade, social scientists have been analyzing the implications of the neoliberal turn in development policy and the implications of market-led agrarian reform for agricultural producers in the global South. Among this work is a spate of recent scholarship celebrating a number of flagship movements, such as the Zapatistas in Mexico or the landless movement in Brazil, which are interpreted as efforts by rural communities to resist the threat posed by the commodification of livelihoods and the privatization of natural resources. In this article, we aim to problematize what we diagnose as the "Polanyian analytic" underlying accounts of the current conjuncture which emphasize the imminent potential of neoliberalism to spawn protective counter-movements of the sort described in The Great Transformation. We do so through an analysis of the Unidad Cafetero Nacional (UCN) movement, an organization of Colombian coffee farmers that effectively mobilized large numbers of cafeteros in the 1990s to protest the liberalization of the global coffee market and the decline of state support for the domestic coffee sector. While the UCN may be read as a struggle to resist the dispossession of Colombian coffee farmers, we argue that it represented a particular segment of rural producers who wanted, first and foremost, a restoration of their relatively privileged status within the political economy of Colombian agriculture. Our interpretation of the UCN suggests that whether movements emerge in response to neoliberalism depends on the political imaginaries of the social actors who would create them, and further, that these imaginaries are produced through processes of class formation over the longue durée that shape the meaning of dispossession in particular contexts.
Keywords: Colombia; agriculture; coffee growers; coffee plantations; commodification; liberalization (finance); neoliberalism; privatization

On Fred Block, Varieties of What? Should We Still Be Using the Concept of Capitalism? - Streeck, Wolfgang (Political Power & Social Theory, 2012)
There are good reasons for preferring the concept of capitalism over that of "market economy." A capitalist economy is one that depends on the commercialization-through-monetarization of ever more social relations. The result is disequilibrium as the normal condition of a society placed under pressure by its "economy" for continuous reorganization in line with a need for ongoing capital accumulation. A capitalist society enlists the possessive individualism of its members as its principal vehicle of social progress, measured as an increase in wealth-as-money. While Polanyian theory has pointed out important features of advanced capitalist societies, there is no need to sacrifice core Marxian concepts for it. Marxian theory helps avoid the trap of political voluntarism, which stipulates a priority of politics in the capitalist political economy or a fundamental difference between "varieties" of capitalism. Moreover, rather than regarding the capitalist economy as by definition "always embedded," political-economic theory must allow for a self-destructive, and indeed socially destructive, tendency of capitalist political economies to "disembed" themselves by struggling free from social controls and dictating to social life the imperatives of market efficiency and a market-conforming distribution of life chances.
Keywords: BLOCK, Fred L.; Marxist philosophy; always embedded economy; capitalism; equilibrium (economics); saving and investment; social control; social theory; varieties of capitalism

Fight or Acquiesce? Religion and Political Process in Turkey's and Egypt's Neoliberalizations - Tuğal, Cihan (Development & Change, 2012)
The Polanyian expectation that disruptive marketization will lead to movements and policies that seek to 'embed' the market in society needs to be tempered by closer scrutiny to historical, religious and political contexts. This article studies how movements respond to marketization. The analysis proceeds through a comparison of the Turkish and Egyptian neoliberalizations, religious movements of the last decades, secular opposition, and finally recent processes, which have led to generally different social takes on neoliberalism. The irony of the Turkish case is that with the empowerment of the Islamists, religious opposition to neoliberalism was muted and secular opposition further marginalized and labelled as 'anti-democratic'. As a result, free market policies were not only sustained, but deepened and intensified, turning Turkey into a neoliberal 'success story'. The (thus far) sustained mobilization of youth and labour in Egypt makes a direct imitation unlikely. Another major factor that would prevent a 'Turkish' solution to Egypt's crisis is the contrasting structure of the religious fields. Moreover, while the passive revolution has further solidified the professional and unified religious field in Turkey, the revolutionary process in Egypt seems to reinforce the fragmentation of the religious field. The article points out that making Islam compatible with neoliberalism would be more difficult in a country with a fragmented religious field, such as Egypt. Although neoliberalism was imposed from above and resisted from below in both nations, in Turkey it came to be embraced in the name of Islam and democracy, whereas in Egypt it remains an imposition and popular struggles against it persist. It is suggested that this process and field-based approach to a Polanyian problem can also shed new light on discussions about 'actually existing neoliberalisms'.
Keywords: Egypt; Turkey; Turkey - economic conditions - 1960; economic conditions in Egypt - 1952; economic policy; economics - religious aspects - Islam; neoliberalism; religion & politics

Understanding the “economization” of social formations - Jessop, Bob (The marketization of society: economizing the non-economic - Editors - Uwe Schimank, Ute Volkmann, 2012)
A critical review of nine dimensions of economization of social relations and their repercussions on societal dynamics. Discusses fictitious commodification, financialization, finance-dominated accumulation, and issues of ecological dominance. Bibliographic note: Book contains selected papers from conference on Marketization of Societies, organized at Bremen University, 1-2 June 2012. This is the pre-print version of a planned conference collection with a commercial publisher.
Keywords: fictitious commodification; fictitious commodities; financialization